Multi-Layered Pawning in Indonesia’s Agrarian Sector: Islamic Legal Challenges and Sustainable Development Implications: Gadai Bertingkat dalam Masyarakat Agraris Indonesia : Dinamika Hukum Islam dan Implikasi bagi Pembangunan Berkelanjutan - Jannah, Nurfaidatul; Rahyu, Putri; Mulyati, Suci; Aisya , Hana Putri (Sharia and Law Faculty of Sunan Kalijaga Islamic State University Yogyakarta, 2024)
Abstract: This study investigates the practice of multi-layered pawning in Rato Village, Indonesia, which is often conducted without formal written agreements, thereby exposing the original landowner (rāhin) to significant risks. In such arrangements, pawned land is frequently transferred to a third party without the knowledge or consent of the initial land pawn initiator, leaving the rāhin in a vulnerable economic position. From an Islamic legal perspective, this practice raises critical concerns regarding the principles of justice, transparency, and the protection of property rights—core foundations of Shariah. Although initially regarded as a form of ʿurf (local custom) that was socially accepted, the practice has evolved into ʿurf fāsid (corrupt custom) as it increasingly causes harm to the rāhin and contravenes the Shariah principle of justice. This research employs a qualitative approach. Data were collected through in-depth interviews with local residents and village leaders, as well as a review of relevant literature on Islamic law and sustainable development. The findings indicate that multi-layered pawning not only undermines the economic stability of landowners but also poses broader threats to the economic, social, and environmental sustainability of agrarian communities. Through strict oversight, the implementation of written agreements, and enhanced education in Shariah-based financial literacy, pawning practices can be redirected to promote equitable and sustainable economic development within agrarian societies. This research contributes to the discourse on pawning law in Indonesia and offers policy insights for improving welfare and sustainability in rural Islamic communities. Abstrak: Penelitian ini mengkaji praktik gadai berlapis di Desa Rato, Indonesia, yang sering dilakukan tanpa perjanjian tertulis formal, sehingga mengekspos pemilik tanah asli (rāhin) pada risiko yang signifikan. Dalam skema ini, tanah yang digadaikan seringkali dialihkan kepada pihak ketiga tanpa sepengetahuan atau persetujuan inisiator gadai tanah awal, meninggalkan rāhin dalam posisi ekonomi yang rentan. Dari perspektif hukum Islam, praktik ini menimbulkan kekhawatiran serius terkait prinsip keadilan, transparansi, dan perlindungan hak milik—landasan utama Syariah. Meskipun awalnya dianggap sebagai bentuk ʿurf (kebiasaan lokal) yang diterima secara sosial, praktik ini telah berkembang menjadi ʿurf fāsid (kebiasaan korup) karena semakin merugikan rāhin dan bertentangan dengan prinsip keadilan Syariah. Penelitian ini menggunakan pendekatan kualitatif. Data dikumpulkan melalui wawancara mendalam dengan penduduk lokal dan pemimpin desa, serta tinjauan literatur terkait hukum Islam dan pembangunan berkelanjutan. Temuan menunjukkan bahwa praktik gadai berlapis tidak hanya mengganggu stabilitas ekonomi pemilik tanah tetapi juga menimbulkan ancaman yang lebih luas terhadap keberlanjutan ekonomi, sosial, dan lingkungan komunitas agraris. Melalui pengawasan yang ketat, implementasi perjanjian tertulis, dan peningkatan literasi keuangan berbasis Syariah, praktik gadai dapat diarahkan kembali untuk mempromosikan pembangunan ekonomi yang adil dan berkelanjutan di masyarakat agraris. Penelitian ini berkontribusi pada pembahasan mengenai hukum gadai di Indonesia dan memberikan wawasan kebijakan untuk meningkatkan kesejahteraan dan keberlanjutan di komunitas Islam pedesaan.